Embedded poetics and surrounding politics of a coastal squatter settlement - Tiwari, Reena (Callwey, Munich, 2009)
This article explores the poetics of built environment at Wedge, a squatter community located on the Western Australian coastline, and uncovers its surrounding politics. Built and un-built patterns at Wedge are chaotic, organic and ambiguous, and yet there are glimpses of a poetic order within the decayed fragments from within its vernacular built form. The article explores this poetic order and further un-layers the politics of the place by revealing the desires of different stakeholders involved in its ‘planned development’. Are the poetics at Wedge under threat from the nature of the political game being played here? Is the very act of ‘ordering and planning’ this place going to result in a loss of its cultural significance, and the creation of a place based on the conflicting desires of the various stake-holders?